Influence of Biologically Active Substance “STEMB” on a Morphofunctional Condition of a Liver and Kidneys of Rats at an Experimental Hepatorenal Syndrome - D.A. Areshidze,; L.D. Timchenko,; M.A. Kozlova,; I.A. Syomin,; I.V. Rzhepakovsky,; S.I. Piskov ,; V.N. Vakulin, (Journal of Pharmacy and Nutrition Sciences, 2015)
In this investigation, we revealed that application of the biostimulating tissue preparation based on chicken embryos (“STEMB”) at experimental hepatorenal syndrome showed improvement of the morphofunctional parameters of a liver. Under the influence of a biostimulator the relative mass of a liver considerably decreased and biochemical markers of a condition of a liver (total bilirubin, ALT, AST) returned to normal. Besides, under the influence of “STEMB” the tendency to normalization of mitotic, apoptotic and binuclear cells index of liver tissues and considerable decrease in a necrotic index is observed. Results of the research conducted by us allow to make a conclusion on possibility of inclusion of “STEMB” in a complex therapy of HRS for treatment of the injuries of a liver which are its main reason.